(untitled) (Interdisciplinary Studies Journal, 2025)
As a consequence of Brazil’s aging population, there is an increasing participation of elderly individuals in the labor market. Many of them are employed in the informal sector under precarious working conditions, without protective measures, and are exposed to the risks of serious occupational accidents. The objective of this research was to analyze the epidemiological characteristics of occupational accidents among elderly people in Brazil, as studies on this topic are scarce. To this end, an exploratory, cross-sectional, retrospective, and descriptive study was conducted with a quantitative approach, based on records of serious occupational accidents in Brazil, made available by the Ministry of Health through the Notification Diseases Information System, covering the years 2010, 2015, and 2020. The study evaluated the relationships of occupational accidents in elderly individuals with incidence density, education level, employment situation, sex, ethnicity, occupation, locality, time, type of accident, affected body parts, notifications, and outcomes. The results indicated an increase in the number of accidents, underreporting, and specificities in the occupational accidents involving elderly individuals, reflecting the need for further studies and the adoption of strategic prevention and health promotion measures, as well as more appropriate protection policies for these workers.